Effect of Tempeature of Incubation on the Growth, Sporulation and Secondary Metabolites Production of Aspergillus umbrosus - Sood*, Manjulata (Journal of Phytology, 2011)
Temperature is one of the most important factors influencing growth, sporulation and survival of the microorganisms. On a certain optimum temperature microorganisms will grow normally and will produce antibiotic. In this study the cultures of A. umbrosus (Bainier & Sartory) were grown on the modified RichardÃ¢â‚¬â„¢s medium and then incubated at different temperature, i.e.; 15, 20, 25, 26, 30, 35, 40, 45 and 50Ã‚Â°C for 12 days at pH 5. In respect of the incubation temperature Aspergillus umbrosus has shown a very narrow range of tolerance. Below 20Ã‚Â°C, growth rate was very less with minimum sporulation and light yellow colouration of the medium.Ã‚Â Optimum growth occurred at 30Ã‚Â°C with equally good growth at 26Ã‚Â°C. This gives a range of 26-30Ã‚Â°C for its best growth. It tolerated temperature up to 35Ã‚Â°C, beyond which it did not grow at all, there were no growth visualized at 40, 45 and 50Ã‚Â°C Sporulation was also good at 26 and 30Ã‚Â°C with dark-brown coloration of the medium, indicated the secretion of secondary metabolites. At 35Ã‚Â°C the growth and sporulation were negatively affected and the medium colour was also greenish.